Weinreb Amides as Privileged Acylating Agents for Accessing α-Substituted Ketones - Senatore, Raffaele; Ielo, Laura; Monticelli, Serena; Castoldi, Laura; Pace, Vittorio (Synthesis, 2019)
The acylation of α-substituted carbanion-type reagents (MCR1R2X; X = halogen, OR, SR, NR3R4, SeR, etc.) with Weinreb amides constitutes a highly versatile and flexible approach for accessing α-functionalized ketones. In this short review we will present a series of transformations—from our own and the work of others—documenting the general applicability of the methodology. Chemoselectivity is uniformly manifested including for critical substrates featuring additional electrophilic functionalities or sterically demanding elements. Importantly, the stereochemical information contained in the Weinreb amides can be fully transferred to the targeted ketones without affecting the optical purity. The protocol is also applicable to chiral carbanions generated through sparteine-mediated asymmetric deprotonation: the careful design of the experimental procedure allows recycling of the sparteine and the Weinreb ‘amine’ (N,O-dimethylhydroxylamine), thus improving the sustainability perspective of the processes.1 Introduction1.1 The Problem of the Synthesis of α-Substituted Ketones1.2 Weinreb Amides: General Features and Preparation2 Synthesis of α-Substituted Ketones2.1 α-Haloketones2.2 Synthesis of α-Cyanoketones2.3 Synthesis of α-Oxyketones2.4 Synthesis of β-Oxo Thioethers (α-Thioketones)2.5 Synthesis of Chiral α-Oxy and α-Nitrogen Ketones via the Sparteine-Mediated Generation of Optically Active Organolithiums2.6 Synthesis of α-Selenomethyl Ketones2.7 Reactivity of α-Phosphorus Carbanions with Weinreb Amides2.8 Modification of the Weinreb Amide Core: The CLAmP Reagent3 Competing Attack of Nucleophiles at More Reactive Electrophilic Sites than Weinreb Amides4 Conclusions
Keywords: ketones; homologation; carbenoids; chemoselectivity; additions